Development of Media Modules for Pregnant Teenage Mothers using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) - Hapisah; Yuniarti; Eli Rahmawati; Suhrawardi (Jurnal Penelitian Pendidikan IPA, 2025)
Teenage pregnancy is public health issue that impacts maternal and infant health, as well as the continuation of adolescent education. This study aims to develop health education module for adolescent pregnant women using the ADDIE model, assess the module's feasibility based on expert validation and user responses, and test its effectiveness in improving the knowledge of adolescent pregnant women. This study uses the ADDIE development model. The research subjects included adolescent pregnant women in Barito Kuala and Banjar Regencies, South Kalimantan. The research instruments consisted of a validation sheet, user response questionnaire, and pre- and post-test questions. Data analysis was conducted using descriptive quantitative and qualitative methods. The analysis stage indicated low health literacy among pregnant adolescents. The module design was structured with a content structure including learning objectives, materials, illustrations, and evaluation. Expert validation results showed the module was in the feasible category with several revisions in the form of adding specific content and supporting visuals. The trial on respondents showed an increase in knowledge scores, where the average post-test score was higher than the pre-test (p < 0.05). This indicates the module's effectiveness in improving adolescent pregnant women's understanding of healthy pregnancies.